SEJARAH POLITIK HUKUM TERHADAP PERADILAN AGAMA DI INDONESIA - Hamiyuddin Hamiyuddin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
Religious Courts in Indonesia is actually an agency that is quite old, older than the state ministry of religion affairs, it is even older than the Indonesia as it has been around since the advent of Islamic kingdoms in this archipelago. In the Dutch colonial era, judiciary was implemented by siding with Dutch who has legal security. Meanwhile, when the Japanese occupation period, the adjudication was carried out without freedom and independence. Then, a novel milestone for the religion court in Indonesia dates back to the enactment of Law No. 7 of 1989 jo Law No. 3 of 2006 jo Law No. 50 of 2009 on religious courts.